Analise de Elementos Estruturais em Hastes de Paredes Delgadas - Alves, Vancler Ribeiro (2003)
This work intends to evaluate bimoments stresses in thin-walled structures mainly in beams and plane frames. External loads induce to warping and strains due to slenderness of thin profiles in open cross section, essential characteristics of a thin-walled structure. Analytical methods are employed in order to research the structural behavior and bimoments stresses, in a wider aspect that cannot be explained by the theory of thick-walled beams